Evaluación de tres sistemas de tutorado con la aplicación de dos fertilizantes foliares a base de ca y b, para disminuir el aborto de flores y frutos en el cultivo de tomate de árbol (solanum betaceum) en Isinche-Pujili, Cotopaxi - Zapata Chicaiza, Ana Cristina (2014)
The research “Evaluation of three tutoring systems with the application of two foliar based fertilizer and Ca-B, in order to decrease the abortion of flower and fruits in the tomato crop tree (Solanum betaceum) was carried out on the property of Mr. Ricardo Reyes located in Isinche neighborhood, Pujili town, Cotopaxi province. The objectives were: to evaluate and select the most appropriate tutoring system to avoid the fork from branches, to evaluate and determinate the best foliar fertilizer to decrease abortion of flowers and fruits in the tomato crop tree and perform economic analysis treatments. Two factors were raised in the study: tutoring systems fork, tie, and umbrella without tutoring, and foliar fertilizer CaBoron 2.00 cc/lt, Diss Calcium Boro 1.00 cc/lt. and the untreated foliar fertilization, in a factorial arrangement 4x3 in DBCA with three replications….